Prevalence and performance effects of neonatal disease in Thoroughbred and Standardbred foals in South‐Eastern Australia. Issue 5 (23rd February 2021) - Raidal, SL; Hughes, KJ; Eastwell, B; Noble, N; Lievaart, J
Abstract : Background: There is little information on foal mortality and the epidemiology of diseases in the neonatal period in Australian equine breeding enterprises. Methodology: This was a prospective cohort study of 1219 foals on 15 breeding farms in south‐eastern Australia to identify the proportion of foals recognised on farm as abnormal at birth or within the first 48 h postpartum, determine the prevalence and risk factors for neonatal disease and assess the subsequent performance of foals in the study population. Results: Overall, 27 foals died within 6 weeks of birth in the study population (2.2%), 142 foals (11.6%) were reported as abnormal at birth, and 304 (25.3%) were regarded as abnormal in the first 48 h postpartum. Non‐septic orthopaedic disease (NSOD) was the most common abnormality recognised. Premature foals and foals born after dystocia or abnormal parturition were more likely to have clinical abnormalities recognised, but the intensity of nursing care did not predict outcome. Prophylactic administration of antimicrobial drugs was associated with increased mortality and septic disease. Maternal periparturient problems, foal gender, abnormality at birth and the presence of septic disease or neonatal maladjustment were associated with decreased performance outcomes, whereas measures to assess and augment passive immune transfer were associated with improved athletic performance. Conclusions and relevance: Information in the current study is important for the treatment and management decisions on farm and to identify industry welfare and production priorities. Although the incidence of all outcome variables was variable, factors recognised on farm in the peri‐parturient period were predictive of subsequent athletic performance.